Assembly of D1/D2 complexes of photosystem II: Binding of pigments and a network of auxiliary proteins - Knoppová, Jana; Sobotka, Roman; Yu, Jianfeng; Bečková, Martina; Pilný, Jan; Trinugroho, Joko P; Csefalvay, Ladislav; Bína, David; Nixon, Peter J; Komenda, Josef (Plant physiology, 2022)
Photosystem II (PSII) is the multi-subunit light-driven oxidoreductase that drives photosynthetic electron transport using electrons extracted from water. To investigate the initial steps of PSII assembly, we used strains of the cyanobacterium Synechocystis sp. PCC 6803 arrested at early stages of PSII biogenesis and expressing affinity-tagged PSII subunits to isolate PSII reaction center assembly (RCII) complexes and their precursor D1 and D2 modules (D1mod and D2mod). RCII preparations isolated using either a His-tagged D2 or a FLAG-tagged PsbI subunit contained the previously described RCIIa and RCII* complexes that differ with respect to the presence of the Ycf39 assembly factor and high light-inducible proteins (Hlips) and a larger complex consisting of RCIIa bound to monomeric PSI. All RCII complexes contained the PSII subunits D1, D2, PsbI, PsbE, and PsbF and the assembly factors rubredoxin A and Ycf48, but we also detected PsbN, Slr1470, and the Slr0575 proteins, which all have plant homologs. The RCII preparations also contained prohibitins/stomatins (Phbs) of unknown function and FtsH protease subunits. RCII complexes were active in light-induced primary charge separation and bound chlorophylls (Chls), pheophytins, beta-carotenes, and heme. The isolated D1mod consisted of D1/PsbI/Ycf48 with some Ycf39 and Phb3, while D2mod contained D2/cytochrome b559 with co-purifying PsbY, Phb1, Phb3, FtsH2/FtsH3, CyanoP, and Slr1470. As stably bound, Chl was detected in D1mod but not D2mod, formation of RCII appears to be important for stable binding of most of the Chls and both pheophytins. We suggest that Chl can be delivered to RCII from either monomeric Photosystem I or Ycf39/Hlips complexes.
Keywords: Photosystem II Protein Complex; Synechocystis; Chlorophyll; feofytiny; chlorofyl; Pheophytins; Photosystem I Protein Complex; fotosystém I (proteinový komplex); fotosystém II (proteinový komplex)